Production of Iron Castings with Gradient Structure for Special Purpose Equipment by In-Mold Modification of One Base Melt - Smernytskyi, D.; Huliaiev, A.; Fesenko, M.; Melnyk, V.; Fesenko, A. (Science and Innovation, 2022)
Introduction. Modern industry requires constant upgrade or modernization of machinery, hardware, mechanisms, equipment and special tools with improved mechanical and operational characteristics and reduced costs. This can be successfully solved by using parts and elements with a gradient structure in local areas, made of cast iron as the cheapest, most common, and available structural material. Problem Statement. The main disadvantage of the known methods for obtaining cast iron parts with a gradient structure is the need for synchronous smelting of liquid cast irons that have different chemical com positions and properties in two smelting units before pouring the mold. Therefore, it is important to find ways and to develop new methods for manufacturing cast iron castings with gradient structure and properties. Purpose. The purpose of this research is to develop optimal technological modes and parameters of casting parts with a gradient structure, with the use of in-mold modification of a base melt. Materials and Methods. The hydrodynamic and temperature processes in mold have been analyzed with the use of computer simulation the experimental castings have been evaluated by the nature of the fracture macrostructure; the metallographic study; the chemical analysis of cast iron, and the comparison of the hardness of local parts of castings. Results. The main technological parameters influencing the nature of cast iron crystallization and, as a consequence, the formation of gradient structure in castings, are configuration and cross-sectional thickness of the casting wall, material and thickness of the insert, and temperature of poured melt. Technological recommendations that ensure the formation of gradient structure and properties in local parts of castings have been given.